Building Hope: Program for Handling Psychosocial Problems of People Living with HIV/AIDS in Denpasar - Fitasya Khairunnisa; Oman Sukmana; Zaenal Abidin; Juli Astutik (Media Kesehatan Masyarakat Indonesia, 2024)
The research aims to describe the forms of Psychosocial Problems Experienced by People Living with HIV/AIDS (PLWHA) and the programs of the Spirit Paramacitta Foundation to overcome the psychosocial problems of PLWHA. The research location was the Spirit Paramacitta Foundation Denpasar, Bali Province. The research uses a qualitative descriptive. The data collection techniques are through observation, interviews, and documentation. Research subjects and informants were determined purposively. Data analysis techniques refer to the perspective of Miles, Huberman, and Saldana, which includes the processes: data collection, data condensation, data presentation, and conclusion and verification. The data validity techniques used are extended observations and source triangulation. The results of the research show that the psychosocial problems of PLWHA at the rejection response stage are in the form of hopelessness, suicidal ideation, and drug use, while at the self-acceptance stage, the psychosocial problems are in the form of social anxiety, feelings of inferiority, social withdrawal, social stigma, and discrimination. Meanwhile, the program for handling psychosocial problems carried out by the Spirit Paramacitta Foundation is a social support program and a social mentoring program. The social support program includes emotional, appreciation, and socialization support. In contrast, the social assistance program includes health service referrals, assistance in taking medication, and home visits. The social services provided by the Spirit Paramacitta Foundation positively impact providing life hope for PLWHA. The practical implications of this research are as a model for institutional social service practices and scientific studies in developing social support for marginalized groups.